Porphyromonas gingivalis exacerbates the progression of fatty liver disease via CD36-PPARγ pathway - Ahn, Ji-Su; Yang, Ji Won; Oh, Su-Jeong; Shin, Ye Young; Kang, Min-Jung; Park, Hae Ryoun; Seo, Yoojin; Kim, Hyung-Sik (BMB reports, 2021)
Periodontal diseases have been reported to have a multidirectional association with metabolic disorders. We sought to investigate the correlation between periodontitis and diabetes or fatty liver disease using HFD-fed obese mice inoculated with P. gingivalis . Body weight, alveolar bone loss, serological biochemistry, and glucose level were determined to evaluate the pathophysiology of periodontitis and diabetes. For the evaluation of fatty liver disease, hepatic nonalcoholic steatohepatitis (NASH) was assessed by scoring steatosis, inflammation, hepatocyte ballooning and the crucial signaling pathways involved in liver metabolism were analyzed. The C-reactive protein (CRP) level and NASH score in P. gingivalis -infected obese mice were significantly elevated. Particularly, the extensive lobular inflammation was observed in the liver of obese mice infected with P. gingivalis . Moreover, the expression of metabolic regulatory factors, including peroxisome proliferator-activated receptor γ (Pparγ) and the fatty acid transporter Cd36, was up-regulated in the liver of P. gingivalis -infected obese mice. However, inoculation of P. gingivalis had no significant influence on glucose homeostasis, insulin resistance, and hepatic mTOR/AMPK signaling. In conclusion, our results indicate that P. gingivalis can induce the progression of fatty liver disease in HFD-fed mice through the upregulation of CD36-PPARγ axis.